ANALISIS PENERAPAN KEBIJAKAN PERKREDITAN BANK STUDI KASUS SEKTOR KREDIT GUNA BHAKTI (KGB) PADA BANK BJB CABANG CIKARANG - Didin Rasyidin Wahyu (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
Banks as financial institutions whose activities which raise funds from the public in the form of savings and channel them back to the community in order to improve the standard of living many of bank can also be said as an institution which won the trust of the public, in this case should try to preserve the feeling of trust society to the bank, then the bank should as much as possible in carrying out its activities both in service, fund raising and distribution, financial and information services in the field of banking activities ets. BJB Cikarang branch is the distribution of funds in which one form of credit in the credit sector Guna Bhakti (BECs), which is expected to help welfare especially the Civil Servants (PNS), Retired Or Other Employees